2006
DOI: 10.1212/01.wnl.0000219765.95038.d7
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan and HCRTR2 candidate gene analysis in a European cluster headache cohort

Abstract: Cluster headache is a complex genetic disorder, with possible phenotypic and genetic heterogeneity compounding attempts at gene identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 46 publications
1
78
0
Order By: Relevance
“…This association was confirmed by a large study performed in Germany, showing that homozygous carriers of the G allele had a twofold increase in risk for the disease [15]. On the contrary, the association was not replicated in a complex dataset of CH patients of Danish, Swedish, and British origin [16].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…This association was confirmed by a large study performed in Germany, showing that homozygous carriers of the G allele had a twofold increase in risk for the disease [15]. On the contrary, the association was not replicated in a complex dataset of CH patients of Danish, Swedish, and British origin [16].…”
Section: Introductionmentioning
confidence: 90%
“…All three of these studies met the inclusion criteria. The study of Baumber et al [16] was performed using three different populations, collected in the UK, Sweden and Denmark. So, in the metaanalysis, the three groups were considered separately ( Table 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Schurks et al [37], it was found that having the G1246A polymorphism in this gene increases the odds ratio of having cluster headaches to 1.97, compared with controls. However, in a study by Baumber et al [38] that evaluated sporadic cluster headaches, no association was seen. These conflicting data suggest that the cluster headache may have a genetic component, whereas the sporadic component would be more difficult to identify as the genetic association.…”
Section: Hypocretin Receptor 2 (Hcrtr2)mentioning
confidence: 91%
“…These studies point to the role that the posterior hypothalamus has as physiological modulator of TNC neurons [43]. A derangement in the hypothalamic orexinergic system has been invoked in CH pathophysiology and genetic studies give support to this idea [44], even if a large multinational genetic study does not confirm this [45].…”
Section: Putative Mechanism Of Action Of Hypothalamic Stimulationmentioning
confidence: 99%